Multi-dimensional modelling of electrostatic forces between atomic force microscopy tip and dielectric surface - Boularas, A. (2013)
In this paper, simulation results for the electrostatic force between an Atomic Force Microscope (AFM) sensor and the surface of a dielectric are presented for different bias voltages on the tip:. The aim is to analyse force-distance curves as AFM detection mode for electrostatic charges. The sensor is composed of a cantilever supporting a conical tip terminated by a spherical apex; the effect of the cantilever is neglected here. Our model of force curve has been developed using the Finite Volume Method. The scheme is based on the Polynomial Reconstruction Operator – PRO-scheme. First results of the computation of electrostatic force for different tip– sample distances, 0 to 600 nm, and for different DC voltage stress applied to the tip, 6 to 25 V, are shown and compared with experimental data in order to validate our approach.